Pelatihan Inovasi Pangan melalui Gerakan Dapur Sehat sebagai Langkah Preventif Stunting di Kabupaten Bangkalan - M. Masqotul Imam Romadlani; Lailatul Muarofah Hanim; Atik Qurrota A’yunin Alisyrofi (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This community service program aims to improve the knowledge and skills of Posyandu (integrated health service post) cadres and mothers regarding stunting and nutritional interventions. These nutritional interventions are implemented by providing additional nutritious food for toddlers through the Gerakan Dapur Sehat (healthy kitchen movement). The additional food is intended to fulfill balanced nutrition by utilizing local food ingredients. This community service activity applies a participatory training method combined with demonstrations and direct practical guidance. This activity was carried out in several stages, namely planning, preparation, implementation, and evaluation. The training was held in Sanggra Agung Village, Socah District, Bangkalan Regency, on Saturday, September 13, 2025. Twenty-one posyandu volunteers, along with several mothers of toddlers, attended this community service activity. Through this program, the training participants successfully practiced making supplementary food for toddlers using easily available food ingredients. Participants made mackerel rice puree with carrots, macaroni and cheese with minced chicken, and sweet corn and yellow squash puree. In addition to gaining knowledge and skills about complementary foods for infants, participants were also equipped with the use of processing tools and the appropriate food texture based on the infants' ages.